Determination of the postprandial cut-off value of triglyceride after a daily meal corresponding to fasting optimal triglyceride level in Chinese subjects - Xie, Yingying; Guo, Liling; Chen, Hao; Xu, Jin; Qu, Peiliu; Zhu, Liyuan; Tan, Yangrong; Zhang, Miao; Wen, Tie; Liu, Ling (Frontiers in Nutrition, 2023)
According to the 2021 consensus statement about triglyceride (TG)-rich lipoproteins and their remnants from the European Atherosclerosis Society (EAS), fasting TG level < 1.2mmol/L is regarded as optimal, otherwise considered as non-optimal TG (NoTG). However, the postprandial cut-off value after a daily meal corresponding to a fasting TG level of 1.2 mmol/L has not been explored. 618 inpatients were recruited in this study. 219 subjects had fasting TG levels < 1.2 mmol/L (i.e. OTG group), and 399 subjects had fasting TG levels ≥ 1.2 mmol/L (i.e. NoTG group). levels of blood lipids were monitored at 0, 2 and 4 h after a daily Chinese breakfast according to their dietary habits. Receiver operating characteristic (ROC) curve analysis was used to determine the postprandial cut-off value corresponding to the fasting TG level of 1.2 mmol/L. Kappa statistics was performed to determine the consistency between fasting and postprandial cut-off values. Postprandial levels of TG and RC significantly elevated and peaked at 4 h after a daily breakfast in two groups (P < 0.05). The optimal cut-off value at 4 h corresponding to fasting TG of 1.2 mmol/L was 1.56 mmol/L. According to the fasting cut-off value, the percentage of patients with NoTG was 64.6% in the fasting state while increased obviously to 73.3-78.4% at 2 and 4 h, respectively, after a daily Chinese breakfast. According to the postprandial cut-off value, the percentage of patients with NoTG at 4 h after a daily Chinese breakfast was 62.6% which was close to 64.6% in the fasting state. The Kappa coefficient was 0.551, indicating a moderate consistency between the fasting and postprandial cut-off values in the diagnosis of NoTG. The subjects with NoTG determined by the postprandial TG cut-off value had obviously higher postprandial level of RC (1.2 v.s. 0.8 mmol/L) and percentage of HRC (37.1 v.s. 32.1%) than those determined by the fasting TG cut-off value. We firstly determined TG 1.56 mmol/L as the postprandial cut-off value corresponding to fasting TG 1.2 mmol/L. This could make it more convenient to determine whether TG is optimal or not in the fasting or postprandial state.